RESPON RESPON GURU TERHADAP PENGGUNAAN APLIKASI WORDWALL DALAM PEMBELAJARAN BAHASA INDONESIA - R. Mekar Ismayani; Alfa Mitri Suhara Alfa Eva; Yeni Rostikawati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
Learning media as a liaison between teachers and students. Learning media has an important role in the learning process, especially in the delivery of material (basic competence). Seeing, the Covid-19 pandemic is not yet over, learning media must be chosen appropriately so that learning objectives can still be achieved optimally. Integrating technological advances by utilizing them in learning, especially for teachers in designing multimedia and interactive learning media is urgently needed. Therefore, this study focuses on the teacher's response to the use of the wordwall application as a support for learning Indonesian at school. The purpose of this study is to find out, analyze, and describe the teacher's response to interactive learning media assisted by wordwall applications as a support for learning Indonesian. This study uses a qualitative descriptive research procedure. The results of the research are known from the distribution of questionnaires on the analysis of teacher needs in the use of learning media, it is known from the ten questions given that the average answer is yes by 79.2% and no by 20.8% related to the use of technology-based learning media, knowledge, constraints or the obstacles encountered and the application of the wordwall application in learning Indonesian. Thus it can be concluded that the use of learning media, especially the wordwall application as a technology-based interactive media is needed by teachers in carrying out Indonesian language learning activities.